Structure and function of an acetyl xylan esterase (Est2A) from the rumen bacterium Butyrivibrio proteoclasticus. Issue 5 (25th February 2013) - Till, Marisa; Goldstone, David C.; Attwood, Graeme T.; Moon, Christina D.; Kelly, Willam J.; Arcus, Vickery L.
Abstract Butyrivibrio proteoclasticus is a significant component of the microbial population of the rumen of dairy cattle. It is a xylan‐degrading organism whose genome encodes a large number of open reading frames annotated as fiber‐degrading enzymes. We have determined the three‐dimensional structure of Est2A, an acetyl xylan esterase from B. proteoclasticus, at 2.1 Å resolution, along with the structure of an inactive mutant (H351A) at 2.0 Å resolution. The structure reveals two domains—a C‐terminal SGNH domain and an N‐terminal jelly‐roll domain typical of CE2 family structures. The structures are accompanied by experimentally determined enzymatic parameters against two model substrates, para‐nitrophenyl acetate and para‐nitrophenyl butyrate. The suite of fiber‐degrading enzymes produced by B. proteoclasticus provides a rich source of new enzymes of potential use in industrial settings. Proteins 2013. © 2012 Wiley Periodicals, Inc.